Impact of Anemia on Quality of Life Among Patients on Dialysis with End-Stage Renal Failure - Omar, Rosnah; Kunjukunju, Annamma; Fariza, Nurul (Queeva Publishing, 2024)
Background: Reductions in quality of life among patients with End-Stage Renal Failure (ESRF) can be further compromised by anemia, which is a common complication of ESRF. This study evaluated the impact of anemia on the quality of life among dialysis patients with ESRF in a private dialysis center in Kuantan. Methods: The study used a cross-sectional design conducted on 113 ESRF patients at multiple dialysis centers in Kuantan. Demographic, socioeconomic, and disease status data were collected, and the Kidney Disease Quality of Life (KDQOL) short-version questionnaire was used to assess the patient's quality of life. Statistical analysis was performed using SPSS 26 to identify correlations among patient factors. Results: The study findings revealed that 46.4% have mild anemia, 38.4% have moderate anemia, and 16.2% have severe anemia.76% of respondents rated the quality of life as